Hasil dan Komponen Hasil Kedelai (Glycine max L. Merr) yang Diberi Pemupukan Nitrogen Lanjutan pada Fase Reproduktif (R1) - Helmi Salim; Sosiawan Nusifera; Nyimas Myrna Elsa Fathia (AGROSAINSTEK: Jurnal Ilmu dan Teknologi Pertanian, 2017)
This research aim to determine the effect of continued nitrogen fertilization to reproductive phase on yield and yield components of soybean. The experiment conducted in teaching and research farm, Faculty of Agriculture, University of Jambi from April to September 2014. The experiment arranged in factorial randomized block design with two replications. First factor were four soybean varieties and second factor were dosages of continued nitrogen fertilization consist of 0 kg ha-1 (n0), 40 kg ha-1 (n1), 50 kg ha-1 (n2) and 60 kg ha-1. Measured variables observed were the length of reproductive phase, number of pods per plant, number of filled pods, weight of 100 seeds, and weight of seed per plant. The result showed that nitrogen did not have effect on evaluated varieties. There were differences in length of reproductive phase, number of pods per plant, number of filled pods, and weight of 100 seeds among soybean varieties. The second nitrogen fertilization with different dosages gave significant effect in number of pods per plant, number of filled pods and weight of seed per plant. Four varieties had same yield potential if developed around research area, but to get larger seed size, Anjasmoro variety was highly recommended. The best dosage to increase yield between varieties was n2 (50 kg N ha-1).